1980
DOI: 10.1139/f80-104
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differences and Environments of Mussel Populations in the Maritime Provinces

Abstract: Genetic differences among Mytilus edulis populations from four localities in Atlantic Canada were examined using electrophoretic techniques. On the basis of allele frequency distributions at four loci (LAP-1, PEPTIDASE-2, PGI, PGM), the localities fell into two pairs, paralleling a similar pairing on the basis of values of specific environmental parameters and their variability. Gene flow between environments could be eliminated as an explanation of gene frequency similarity in one of the pairs. The large hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…Further the D values are also highest, when a cold and a warm site are paired. This is in agreement with Gartner-Kepkay et al (1980), who also concluded that environmental factors can explain deficiencies and variation for mussels.…”
Section: Genetic Variationsupporting
confidence: 92%
See 1 more Smart Citation
“…Further the D values are also highest, when a cold and a warm site are paired. This is in agreement with Gartner-Kepkay et al (1980), who also concluded that environmental factors can explain deficiencies and variation for mussels.…”
Section: Genetic Variationsupporting
confidence: 92%
“…Allozymes may have effects on overall fitness and growth rates (Koehn and Gaffney, 1984;Singh and Green, 1984) and therefore selection for the most beneficial enzyme could be the cause for heterogeneity of the allozyme frequencies. This is supported by results from the study of Gartner-Kepkay et al (1980), who found indications in M. edulis that variable environmental parameters are mirrored in populations with variable genomes and thus reflect a functional aspect of adaptability. In D. serra several loci are affected differently, thus we postulate that there is a different sensitivity of the enzyme systems to various environmental selective forces.…”
Section: Balancing Selective Pressuresupporting
confidence: 58%
“…Koehn, 1983;Gosling, 1984}. A large body of information on micro-and macrogeographic variation has accumulated from several polymorphic gene-enzyme systems studied in mussel populations from both North America (Koehn et al, 1976Levinton & Suchanek, 1978;Gartner-Kepkay et al, 1980 and selected areas of Europe (Theisen, 1978;Murdock et al, 1979;Goshng & Wilkins, 1981;Skibinski et al, 1983;Fevolden & Garner, 1986}. As outlined in the preceding section, our electrophoretic survey of Baltic 54ytilus…”
Section: Discussionmentioning
confidence: 98%
“…In addition, samples of C. volutator from DGB clustered with samples from the Gulf of Maine (Einfeldt and Addison 2013), but in our collections from DGB, T. obsoleta was genetically identical to the Bay of Fundy, whereas M. petalum was genetically more similar to samples from eastern Nova Scotia. Population genetic studies in other species also show mixed patterns across this transition zone (e.g., Gartner-Kepkay et al 1980;Dillon and Manzi 1992;Addison and Hart 2004;Evans et al 2004;Kelly et al 2006;Kenchington et al 2006;Jennings et al 2009;So et al 2011;Owen and Rawson 2013;St-Onge et al 2013;Benestan et al 2015;Govindarajan et al 2015), but as these studies only sampled one population in or at the mouth of the bay, they provide little resolution to the boundaries of phylogeographic transition. Although many species of marine invertebrates sampled in the Bay of Fundy appear isolated from populations studied elsewhere, incongruence in the location of the break suggests that the physical boundaries to gene flow across the gyre depend on a variety of factors including both dispersal ability and evolutionary history.…”
Section: Discussionmentioning
confidence: 99%